Application of MIMO Technology to Systems Beyond 3G - Ibikunle Frank; Olowononi Felix (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
The evolution of mobile Broadband over the years has been phenomenal and worthy of attention by academics, researchers, the corporate world and users alike. From the days of the First Generation (1G) through the Third Generation (3G) communication systems, the evolution has continued and has been largely influenced by an ever increasing demand for improved services and greater capacity evident in higher data rates, wider and improved coverage, improved spectral efficiency and lower latency. In response to these demands and to address some of the loopholes of the 3G networks, the 3rd Generation Partnership defined the Long Term Evolution (LTE). LTE though an evolving technology is widely accepted due to its unprecedented promised performance. As the evolution continues, the design of the ‘LTE-Advanced’ is already in progress and has been tagged different names such as the ‘4G’ and ‘Beyond 3G’ (B3G). The main backbones behind these evolutions are technological developments in the underlying mobile radio technology such as multicarrier technology (majorly OFDMA), multiple-antenna technology (MIMO) and the application of packet-switching to the radio-interface through improvements in techniques like adaptive scheduling in both the frequency and spatial dimensions, link adaptation of modulation and code-rate and several modes of fast channel state reporting. This paper is set to present the multiple antenna technology and how it contributes to the delivery of the expectations of the wireless communication systems beyond 3GDOI: http://dx.doi.org/10.11591/ij-ict.v1i2.1482